Estudio de prefactibilidad para el desarrollo de un servicio de reserva de estacionamientos mediante una aplicación móvil - Espinoza Pizarro, Martin Alonso (2020)
The main objective of this project is to propose a new parking alternative to Lima drivers that enables lowering the existing problems due to the current supply shortage in this field as well as the expensive prices established by parking companies. For this reason, it has been proposed a service that includes the functions of searching, making reservations and payment of parking spaces in homes through the application using only a credit card. By the preferential factor method, Lima is determined as the city where the project will be developed. Also, the market study will be carried out by conducting surveys and focus groups. In addition, the demand for the project was determined, with a segmented demand of 114,748 users in search of parking in the first year, over which 18% of the market share would be covered. Finally, the Focus generic strategy and the market penetration pricing strategy were defined. Subsequently, the factor ranking method was used, determining San Isidro as the most appropriate district to locate the administrative offices. Regarding the dimensioning of the service, it was obtained that the limiting factor is the size of the market obtaining a transaction flow of S/3,776,796. In addition, it was detailed the operation of the mobile application through flowcharts, the resources necessary to use, as well as the service operations program for the first year, with which it was determined that approximately 5,000 registered parking spaces would be needed to start the operation. Finally, it was determined that the project requires an investment of S/ 409,164, and by performing the financial evaluation it was obtained a VAN of S/ 2,658,831, a TIR of 264.55%, and a recovery period of less than one year.